APOE interacts with age to modify rate of decline in cognitive and brain changes in Alzheimer's disease. Issue 3 (29th July 2013) - Chang, Yu‐Ling; Fennema‐Notestine, Christine; Holland, Dominic; McEvoy, Linda K.; Stricker, Nikki H.; Salmon, David P.; Dale, Anders M.; Bondi, Mark W.; ,
Abstract: Objective: To determine (1) whether age‐standardized cognitive declines and brain morphometric change differ between Young‐Old patients with Alzheimer's disease (YOAD) and Very‐Old patients with Alzheimer's disease (VOAD), and (2) whether the apolipoprotein E ( APOE ) genotype modifies these neuropsychological and morphometric changes. Methods: Baseline and 12‐month follow‐up neuropsychological and morphometric measures were examined for healthy control subjects and patients with AD. The two AD groups were divided further into subgroups on the basis of the presence of at least one APOE ε4 allele. Results: The YOAD group showed more severe deficits and steeper declines in cognition than the VOAD group. Moreover, the presence of an APOE ε4 allele had a more deleterious effect on the YOAD group than the VOAD group on cognition and brain structure both cross‐sectionally and longitudinally. Conclusions: Results underscore the importance of integrating an individual's age and genetic susceptibility—and their interaction—when examining neuropsychological and neuroimaging changes in the early stages of Alzheimer's disease.